Protein labeling with the labeling precursor [18F]SiFA-SH for positron emission tomography - Wängler, Björn; Niedermoser, Sabrina; Wängler, Carmen (Nature protocols, 2012)
Proteins previously derivatized with the cross-coupling reagent sulfo-SMCC (4-(N-maleimidomethyl)cyclohexane-1-carboxylic acid 3-sulfo-N-hydroxy-succinimide ester sodium salt) can be easily labeled in high radiochemical yields with the silicon-fluoride acceptor (SiFA) reagent [18F]SiFA-SH, obtained via isotopic exchange, by thiol-maleimide coupling chemistry (n = 10). The specific activity of SiFA-SH obtained in a one-step labeling reaction was >18.5 GBq μmol−1 (>500 Ci mmol−1). The number of SiFA building blocks per protein molecule is defined by the previously introduced number of maleimide groups, which can be determined by a simple and convenient Ellman's assay. Not more than two maleimide groups are introduced using sulfo-SMCC, thereby keeping the modification of the protein low and preserving its biological activity.